The relationship between some harmonic abilities and the level of skill performance among elite volleyball players in Palestine - Asfour, Hussein Rafi; Ayesh Rajah, Tariq Ghazi; Mahmoud Asfour, Rafi Hussein (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The aim of this study was to identify the relationship between some harmonic abilities and the level of skill performance of elite volleyball players in Palestine. The study used the descriptive analytical approach. The sample consisted of 12 volleyball players of the Singel Club Champions of Palestine. The Statistical Program for the Social Sciences (SPSS) was used for data analysis. The results showed that there is a positive and statistically significant correlation between overall harmonic abilities and the level of skill performance (p<0.05). The results also showed that most harmonic abilities (rhythmic ability, ability to adapt to changing situations, and ability to link movement) have an impact on the skill performance of the offensive blocking of positions 2, 3 and 4 (p<0.05). The authors recommend the use of harmonic abilities due to their positive impact on skill performance in volleyball. Furthermore, encouraging coaches and those in charge of the training process to use and develop harmonic abilities exercises is crucial, as they are an important, effective, and influential part in improving and developing the skill performance of volleyball players.